Specific inspiratory muscle training does not improve performance or VO2max levels in well trained rowers - Riganas, C. S.; Vrabas, I. S.; Christoulas, K.; Mandroukas, K. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. The purpose of this study was to examine the effects of specific inspiratory muscle training (IMT) on inspiratory muscle strength, maximal oxygen uptake (VO2max), maximal lactate accumulation (Lmax), dyspnea sensation and rowing performance in rowers. Methods. Ninteen well-trained rowers were divided into two groups: IMT (T) and control (C). The T group, in addition to their daily rowing practice, performed IMT by means of a threshold inspiratory muscle trainer for ~0.5h/d, 5 times a week for 6 weeks. The C group participated only in their regular daily rowing training. Prior to the initiation and at the completion of the 6-week IMT program, both groups underwent an incremental treadmill run test to determine VO2max. Maximum inspiratory mouth pressure (PImax) was measured at rest and following the VO2max test. On a separate occasion, rowing performance was evaluated by a 2 000 m all-out effort on a rowing ergometer. Dyspnea sensation was assessed by a modified Borg scale and Lmax was measured by an enzymatic method. Results. Six weeks of IMT significantly (P<0.05) increased resting PImax. Moreover, inspiratory muscle training increased PImax following the VO2max test in the T group. In contrast, no changes in PImax were observed in the C group during the 6-week period. No significant differences were observed between pre- and post-test values in VO2max, dyspnea sensation, Lmax, and 2 000 m race time in both groups. Conclusion. In conclusion, six weeks of IMT increases inspiratory muscle strength by ~28% in highly trained rowers. However, this increase in inspiratory muscle strength does not appear to improve VO2max, dyspnea sensation during exercise, or rowing performance in well-trained rowers.